Physicochemical and biological properties of encapsulated Boesenbergia rotunda extract with different wall materials in enhancing antioxidant, mineralogenic and osteogenic activities of MC3T3-E1 cells - Safiah Saah; Dalad Siriwan; Piyapat Trisonthi; Sawitree Dueramae (Elsevier, 2024)
Boesenbergia rotunda (L.) comprises bioactive compounds with biological and pharmacological properties, especially flavonoid compounds with osteoblastogenesis-stimulating potential. However, the application of B. rotunda in the food and pharmaceutical industry is restricted by its low solubility and stability. Encapsulation becomes an alternative to overcome these restrictions. The purpose study was to encapsulate B. rotunda extract by freeze-drying and to investigate the effects of different wall materials (maltodextrin (MD), gum arabic (GA), and their combination (MDGA)) and extract contents on the physicochemical, bioactive properties and in vitro enhancement of osteogenesis of MC3T3-E1 cells of the obtained encapsulates. The results revealed that encapsulated B. rotunda can reduce cytotoxicity, enhance biological activity, and maintain the stability of bioactive compounds. The MD was a good wall material for yield percentage. However, the values of moisture content Aw, and solubility among all the encapsulated powders were no significant differences, with all encapsulated powders having similar structures based on scanning electron microscopy. Fourier transform infrared spectroscopy confirmed the extract was encapsulated by the selected wall materials. Combining the MD and GA encapsulation agents afforded the best protection of the bioactive compounds, increasing EE (MDGA-7 > MDGA-5), pinostrobin content, TPC, and antioxidant activities (MDGA-5 > MDGA-7). The MDGA-5 and MDGA-7 at 10-50 μg/mL were not toxic to cells and promoted MC3T3-E1 cell viability, while also enhancing the Alkaline phosphatase activity, and promoting matrix mineralization of pre-osteoblast MC3T3-E1 cells after 21 and 28 days. This result showed that MDGA was a suitable wall material for B. rotunda encapsulations and a potential source of bioactive ingredients that could applied in food or pharmaceutical products for osteoporosis prevention.